Guide to economic indicators : making sense of economics (London : Profile Books, 2010)
It is essential in business and many professions today to have a thorough understanding of economic information. Written for the non-specialist, this highly accessible guide provides the keys to understanding all the major and many lesser economic indicators: what they are, the areas they cover, their reliability, and how and why to interpret them. It contains chapters covering: GDP (Gross Domestic Product),GNP (Gross National Product) and GNI (Gross National Income) ... Growth, trends and cycles ... Population, employment, unemployment... Government... Consumers... Investment and savings... Industry and commerce... Balance of payments... Exchange rates... Money and financial marketsNow in its 7th edition this fully updated, revised guide is invaluable for anyone who needs or simply wants to have the underlying economic realities of the world we live in clearly explained.
Includes index.
nmn, 7/12/16
Loan
Keywords: Social sciences; Economic indicators; Economics